Caregivers acceptability of pharmacological and non-pharmacological interventions in nursing homes in Iceland - Kristel Þórðardóttir 1998- (2022)
Behavioral and Psychological Symptoms of Dementia (BPSD) create numerous complications for residents and employees in nursing homes and other assisted living facilities. This quantitive study was a replication of Baker and LeBlanc's (2011) study "Acceptability of Interventions for Aggressive Behavior in Long-Term Care Settings: Comparing Ratings and Hierarchical Selection." The study examined caregiver‘s acceptability of both pharmacological and non-pharmacological interventions for behavioral disturbances in nursing homes residents in Iceland. Participants were recruited online using a convenience sampling method. Caregivers were asked to evaluate three treatments; (1) Communication Treatment, (2) Light and Sensory Treatment and (3) Pharmacological Intervention. The results suggest that caregivers find the Communication Treatment the most acceptable intervention in geriatric care in Iceland, then Light and Sensory Treatment, but Pharmacological intervention least acceptable. This is the first study in Iceland to evaluate how acceptable different interventions for behavioral disturbances in nursing homes are to caregivers. Understanding what others believe to be the best course of action will assist us in making better decisions to enhance the quality of life for individuals with NCDs. Keywords: Acceptability, Geriatric care, Caregivers, Communication Treatment, Light and Sensory Treatment, Pharmacological Intervention Krefjandi hegðun eldri einstaklinga skapar fjölmarga erfiðleika fyrir íbúa og starfsmenn á hjúkrunarheimilum og öðrum þjónustustofnunum. Þessi megindlega rannsókn var byggð á rannsókn Baker og LeBlanc (2011) „Acceptability of Interventions for Aggressive Behaviour in Long-Term Care Settings: Comparing Ratings and Hierarchical Selection.“ Tilgangur rannsóknarinnar var að fræðast um viðhorf og val umönnunaraðila á meðferðum við krefjandi hegðun hjá eldri einstaklingum með taugavitræna sjúkdóma sem búa á hjúkrunarheimilum. Í rannsókninni var kannað hversu ásættanleg aðstandendum finnst bæði ...